Exposed endoscopic full-thickness resection without laparoscopic assistance for gastric submucosal tumors: A systematic review and pooled analysis. Issue 6 (June 2022) - Granata, Antonino; Martino, Alberto; Ligresti, Dario; Tuzzolino, Fabio; Lombardi, Giovanni; Traina, Mario
Abstract: Background: Exposed endoscopic full-thickness resection (Eo-EFTR) is emerging as a promising minimally invasive alternative to surgery for the treatment of deep gastric submucosal tumors (G-SMTs). However, literature concerning this subject is heterogeneous and data mostly come from relatively small retrospective studies. Aims: We aimed to perform a pooled analysis of published data with regard to gastric Eo-EFTR, providing a pooled estimate of technical and clinical outcomes. Methods: The protocol was registered in PROSPERO. MEDLINE and EMBASE databases were searched for studies published from 1998 to 2020. The primary outcomes were complete resection and surgical conversion rates. The secondary outcomes were overall and selected major adverse events rates. The Forest plots on primary and secondary endpoints were produced based on fixed and random effect models. Results: Nineteen studies including 952 Eo-EFTR-treated G-SMTs were included. The pooled estimate of the complete resection rate and surgical conversion rates was 99.3% and 0.09%, respectively. The pooled estimate of overall major adverse events, delayed bleeding, delayed perforation and peritonitis, abdominal abscess and/or abdominal infection was 0.29%, 0.14%, 0.14%, and 0.12%, respectively. Conclusion: Gastric Eo-EFTR has a high rate of complete resection with a low surgical conversion rate. It appears to be relatively safe and might represent a non-inferior minimally invasive alternative to surgery in selected cases.